2016
DOI: 10.1175/jcli-d-15-0389.1
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Climate Simulations Using GFDL HiRAM with a Stretched Global Grid

Abstract: An analytic Schmidt transformation is used to create locally refined global model grids capable of efficient climate simulation with gridcell widths as small as 10 km in the GFDL High-Resolution Atmosphere Model (HiRAM). This method of grid stretching produces a grid that varies very gradually into the region of enhanced resolution without changing the topology of the model grid and does not require radical changes to the solver. AMIP integrations were carried out with two grids stretched to 10-km minimum grid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
131
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 138 publications
(152 citation statements)
references
References 57 publications
0
131
0
Order By: Relevance
“…We will also present results from the shallow‐water configurations of the GFDL spectral core and of FV 3 . In addition, for FV 3 , we also present results from the nonhydrostatic solver and for a nonuniform stretched grid (Harris et al, ). It is found that while there are differences between each of the cores and the different solver configurations, the test case behaves similarly in all of the cores and configurations tested.…”
Section: Results From Three Dynamical Coresmentioning
confidence: 98%
“…We will also present results from the shallow‐water configurations of the GFDL spectral core and of FV 3 . In addition, for FV 3 , we also present results from the nonhydrostatic solver and for a nonuniform stretched grid (Harris et al, ). It is found that while there are differences between each of the cores and the different solver configurations, the test case behaves similarly in all of the cores and configurations tested.…”
Section: Results From Three Dynamical Coresmentioning
confidence: 98%
“…- Harris et al (2016) tracked tropical cyclones in multiple climate datasets with regional resolution ranging from ∼ 75 km to ∼ 10 km. Candidates were identified from a minimum smoothed SLP no greater than 1013 hPa with 2 hPa closed contour not encircling another minimum.…”
Section: -Sugi Et Al (2002) Tracked Tropical Cyclones In a T106mentioning
confidence: 99%
“…All events are associated with a low pressure system, of which eight (44 %, orange tracks in Fig. 9 methodology of Harris et al (2016) as implemented in Murakami et al (2015). Note that the low pressure systems of the top four events do not classify as tropical cyclones, showing the precipitation potential of non-tropical cyclone low pressure systems in the model.…”
Section: Meteorological Conditionsmentioning
confidence: 99%